Translation Methods in Peter Rabbit 2018 Animated Film - Dien Novita; Mayasari Mayasari (CV. Rayyan Dwi Bharata, 2026)
The purpose of this study is to analyze how translation is carried out in the Indonesian subtitles of the film Peter Rabbit, using Peter Newmark's (1988) theory as a guide. This study focuses on four methods that emphasize the source language: word-for-word translation, literal translation, faithful translation, and semantic translation. This study uses a descriptive qualitative method, selecting 35 subtitle examples from the film and comparing them textually. The results show that literal translation is the most common, used in 17 of the 35 examples (48.6%), followed by semantic translation (20.0%), word-for-word translation (17.1%), and Faithful translation (14.3%). The use of literal translation shows that translators strive to preserve the original structure while ensuring that the subtitles are clear and easy for viewers to understand. This method is effective for children's films where accuracy and simplicity are very important. This study adds value to the field of audiovisual translation by demonstrating a practical approach to translating subtitles for family-friendly content.